LBO : um método de abordagem que respeita as singularidades corporais em um ensino contemporâneo para o balé cássico - Almeida, Uriel Trindade de (2015)
This research has the theme "LBO® - Lateral Box Organization", which translated into Portuguese means Lateral Organization of Boxes, proposed by the dancer / physiotherapist Juliana Stagliorio, creator of this method of approach. This one proposes another look at the teaching of classical ballet that respects and works more specifically the corporal singularities, providing a teaching that goes beyond the mechanistic technique of repetition of the movements encoded in a body called "perfect". Starting from bibliographical reviews on various themes related to dance and education and field research at the Juliana Stagliorio School of Dance, we collected theoretical material to support this work. In the field it was observed and analyzed the methodology of applied teaching for singular bodies of three classes: Preparatory, with students from 5 to 7 years of age; a group of adult ballet beginners aged 29 to 40; and one of LBO Workout, taught by the ballet dancer / teacher / physiotherapist Juliana Stagliorio. The methodology was based on a qualitative case study, developed through bibliographical revisions, interviews with the creator of the method, video records and report writing of observation of the classes for analysis. The data collected in the field (observations, interviews) provide information about how this pedagogical action is performed and how this process of "other look" happens in practice, having the help of several theorists pertinent to the theme. In this way, the aim was to look at the teaching of classical non-mechanic ballet, which respects the singularities of bodies, in a pedagogical action that aims beyond technique.